Pediatric Cushing's disease: Case reports and retrospective review - Renata Pomahacova; Petra Paterova; Eva Nykodymova; Josef Sykora; Michal Krsek (Biomedical Papers, 2024)
Background. We report four pediatric subjects with Cushing's disease (CD) diagnosed in the Czech Republic. We focus on initial symptoms of Cushing's syndrome (CS) which can lead to early diagnosis, on typical symptoms of CS in children, their age and sex distribution, the mean length of symptoms prior to diagnosis, indication for examination, post-cure growth, sexual development and pituitary function in our four CD patients after transsphenoidal pituitary surgery (TSS). We describe the diagnostic process leading to confirmation of CD and we emphasize the biochemical and radiological diagnostic difficulties. Conclusions. Pediatric CD has a number of features distinct from adult CD. Our retrospective analysis confirmed the presence of growth retardation and change in facial appearance with development of moon face as the first symptoms of CS. According to our observation, growth retardation is prior to development of moon face. The other typical symptoms frequently seen in pediatric patients are pseudo-precocious puberty in both sexes, hirsutism in pubertal girls due to excessive adrenal androgen secretion and pubertal delay. A corticotropin-releasing hormone (CRH) test and especially bilateral inferior petrosal sinus sampling for ACTH (BIPSS) contribute to confirming the diagnosis of CD and excluding ectopic ACTH syndrome in children with unvisible adenoma on pituitary magnetic resonance imaging (MRI).